Advancing agricultural sustainability through microalgae biotechnology innovations - Rocha Salazar, João (fi=Turun yliopisto|en=University of Turku|, 2024)
Technological advancements in agriculture have significantly contributed to the rise of soilless techniques such as hydroponic farming, claiming to be a more sustainable approach when compared to soil-based agriculture. Despite the efforts to be more sustainable, nutrient concentrations are far from optimized and hydroponic wastewaters are overloaded with nutrients when discharged into nature. In the present study, the principles of circular economy were applied to explore the potential of microalgae biotechnology for purifying hydroponic wastewaters from a commercial greenhouse. Initially, the quality of the hydroponic wastewater was evaluated at laboratory scale, and screening trials were performed to identify promising microalgae species. Afterwards, the process was scaled-up to a glass greenhouse using an indoor photobioreactor (PBR) equipped with artificial light. Finally, several microalgae species were tested for their potential as novel plant biostimulants and biopesticide agents. The laboratory results confirmed the quality of the hydroponic wastewaters and identified several photosynthetic microorganisms capable of growing in it. Two promising species were selected for the experiments using the indoor PBR. In our first attempt, the microalgae Scenedesmus obliquus was cultivated in continuous mode, recirculating over 1000L of hydroponic wastewater for more than a month of operation. In the following attempt, a batch mode cultivation was performed using the microalgae Tetradesmus obliquus. The species achieved a density of over 6 g L−1 and a maximum N uptake of 132.5 ± 14.0 mg g−1. The experiments regarding the bioactivities of microalgae biomass revealed that extracts from Chlorella sorokiniana can inhibit fungal growth by as much as 50%. In addition to that, extracts from T. obliquus increased the fresh weight of lettuce by more than 15%. Overall, this work reveals the potential of microalgae biotechnology to accelerate sustainable solutions in agriculture.